Examining transitions in loneliness for people without and with moderate and severe disabilities. - Pagán-Rodríguez, Ricardo Braulio (Taylor & Francis, 2020)
Purpose: To investigate how disability affects the levels of loneliness reported by people living in Germany. In particular, we are interested in analysing the transitions into and out of loneliness but incorporating a dynamic approach of disability (i.e., disability trajectories). Method: Drawing data from the German Socio-Economic Panel for the years 2013 and 2017 and using a three-item version of the UCLA Loneliness Scale, we construct a balance panel of individuals and estimate linear regression models on loneliness, and probit models to predict the likelihood to become lonely or exit from loneliness. Results: We find a positive association between disability and loneliness (especially for those people who are severely limited). The frequency of contacts with family, friends, etc., the number of close friends and the participation in volunteering, sports, cultural and religious events reduce loneliness. Furthermore, we find that those individuals making the transition into a moderate/severe disability and also those recovering totally from a severe disability are more likely to become lonely in 2017. Conclusions: From a public health policy perspective, it is necessary to undertake the design and implementation of instrumental, emotional and social support for people with disabilities. A higher engagement in social activities (e.g., social gatherings, cultural and leisure activities) and the elimination of barriers (e.g., structural and environmental) may become key elements to preventing loneliness.
https://openpolicyfinder.jisc.ac.uk/id/publication/20617
Keywords: Personas con discapacidad - Aspectos psicológicos; Germany; Disability; Loneliness; Transitions; Longitudinal data